SINERGI HALODOC DALAM MUTU PELAYANAN RUMAH SAKIT DI MASA PANDEMI COVID 19 - Putra, Putu Aditya; Suryanata, I Gusti Ngurah Putra (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.04.TAHUN.2021, 2021)
One of the developments in information system technology in the health sector via the internet is E-health. The Medical Teleconsultation solution offered is very helpful for the Indonesian health system in screening patients with a risk of Covid 19. Halodoc is the number 1 health application in Indonesia. The purpose of this study was to determine the Halodoc synergy in the quality of hospital services on patient satisfaction, trust, and loyalty. This research was conducted in a type c hospital in collaboration with Halodoc in Denpasar, namely Surya Husada Hospital and Bali Royal Hospital. Taken a sample of 50 respondents at each hospital. Data collection techniques using a questionnaire. This study uses data analysis methods using Smart PLS software. The results of this study were Halodoc Medical teleconsultation proved to have a positive and significant effect on patient satisfaction, patient confidence and patient loyalty. The quality of hospital services is proven to have a positive and significant effect on patient satisfaction and patient confidence. Halodoc Medical Teleconsultation proved to have a positive and significant effect on the quality of hospital services. Related to the research results, it was found that some people still trust their health fully by consulting directly with medical personnel at the hospital. This research will become an illustration to see the development of medical teleconsultation in Indonesia. As well as indirectly seeing to what extent the role of Halodoc Medical Telecosultation is able to provide optimal health services in the midst of the Covid 19 pandemic.